Exploring the Potential of Novel Gadolinium-Free Contrast Agents in MRI: A Pilot Study in a Mexican Cohort - Juan Felix Ramirez; Matilda Munoz (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Gadolinium-based contrast agents (GBCAs) have been instrumental in enhancing MRI diagnostic capabilities. However, concerns about gadolinium deposition and associated adverse events have spurred research into safer alternatives. This pilot study aimed to evaluate the safety and efficacy of a novel gadolinium-free contrast agent (GBCA-X) in a Mexican cohort. Methods: This prospective, single-center study enrolled 30 adult patients scheduled for contrast-enhanced MRI examinations. Patients received GBCA-X intravenously, and MRI scans were performed using standard protocols. Image quality, contrast enhancement, and adverse events were assessed. Results: GBCA-X provided adequate contrast enhancement in all patients, enabling clear visualization of target tissues and pathologies. Image quality was comparable to that achieved with GBCAs. No immediate or delayed adverse events were reported. Conclusion: This pilot study suggests that GBCA-X is a safe and effective alternative to GBCAs. Further studies with larger cohorts and diverse patient populations are warranted to confirm these findings and establish the role of GBCA-X in clinical practice.